2009
DOI: 10.1085/jgp.200910285
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ca2+ syntillas increases spontaneous exocytosis in mouse adrenal chromaffin cells

Abstract: A central concept in the physiology of neurosecretion is that a rise in cytosolic [Ca2+] in the vicinity of plasmalemmal Ca2+ channels due to Ca2+ influx elicits exocytosis. Here, we examine the effect on spontaneous exocytosis of a rise in focal cytosolic [Ca2+] in the vicinity of ryanodine receptors (RYRs) due to release from internal stores in the form of Ca2+ syntillas. Ca2+ syntillas are focal cytosolic transients mediated by RYRs, which we first found in hypothalamic magnocellular neuronal terminals. (sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…These findings suggest that the Ca 2+ from syntillas elicited by either type 1 RyRs (in nerve terminals) or type 2 (in chromaffin cells) is released into a microdomain different from the one where the final exocytic step occurs. Moreover, in chromaffin cells, we have found that syntillas that arise from RyR2s suppress exocytosis monitored amperometrically (33). A study on the porcine stress syndrome indicates that a similar mechanism may be present in the parvocellular neurons.…”
Section: Role Of Ryr1 In Exocytosismentioning
confidence: 75%
See 1 more Smart Citation
“…These findings suggest that the Ca 2+ from syntillas elicited by either type 1 RyRs (in nerve terminals) or type 2 (in chromaffin cells) is released into a microdomain different from the one where the final exocytic step occurs. Moreover, in chromaffin cells, we have found that syntillas that arise from RyR2s suppress exocytosis monitored amperometrically (33). A study on the porcine stress syndrome indicates that a similar mechanism may be present in the parvocellular neurons.…”
Section: Role Of Ryr1 In Exocytosismentioning
confidence: 75%
“…Next, sparks were found in smooth muscle (39) (40-42). Thus, the microdomain in smooth muscle is the basis for Ca 2+ to exert multiple, even opposite, effects and provides a precedent for their unexpected action in chromaffin cells (33).…”
Section: +mentioning
confidence: 99%
“…The three phases of LDCV exocytosis have been attributed to different vesicle pools, but it is uncertain whether these pools represent physically distinct types of vesicles, or simply different functional states. In addition, spontaneous exocytosis of LDCVs has also been described in chromaffin cells, and also appears to be regulated by Ca 2+ [30]. …”
Section: Endocrine Exocytosismentioning
confidence: 99%
“…Calcium syntillas do not cause exocytosis in magnocellular neurons [30] or in chromaffin cells [31] but make significant contributions to initiating exocytosis in dorsal root ganglion neurons [32]. In chromaffin cells, the syntilla calcium is released into a microdomain that is different from the site of exocytosis [31] where it appears to suppress exocytosis [33]. Thus, in multiple neurons, RyRs physically couple to L type calcium channels to generate small transient calcium syntillas and contribute to depolarization evoked global calcium increases.…”
Section: Discussionmentioning
confidence: 99%